2004
DOI: 10.1021/bi049762n
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Action of the Fragile Histidine Triad, Fhit:  Isolation of a Covalent Adenylyl Enzyme and Chemical Rescue of H96G-Fhit

Abstract: The human fragile histidine triad protein Fhit catalyzes the Mg(2+)-dependent hydrolysis of P(1)-5'-O-adenosine-P(3)-5'-O-adenosine triphosphate, Ap(3)A, to AMP and ADP. The reaction is thought to follow a two-step mechanism, in which the complex of Ap(3)A and Mg(2+) reacts in the first step with His96 of the enzyme to form a covalent Fhit-AMP intermediate and release MgADP. In the second step, the intermediate Fhit-AMP undergoes hydrolysis to AMP and Fhit. The mechanism is inspired by the chain-fold similarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 27 publications
1
45
0
Order By: Relevance
“…The prominent putative Table 3. Tobacco smoke-exposed BECs, adenocarcinoma, and SCC exhibit common and distinct allelic loss patterns (30,31). Frequent allelic losses, homozygous deletions, and aberrant transcripts of the FHIT gene have been described in a high percentage of lung tumors (30).…”
Section: Discussionmentioning
confidence: 99%
“…The prominent putative Table 3. Tobacco smoke-exposed BECs, adenocarcinoma, and SCC exhibit common and distinct allelic loss patterns (30,31). Frequent allelic losses, homozygous deletions, and aberrant transcripts of the FHIT gene have been described in a high percentage of lung tumors (30).…”
Section: Discussionmentioning
confidence: 99%
“…Assay of Ap 3 A and Ap 4 A Hydrolysis-A coupled assay was applied to determine the rate of hydrolysis of Ap 3 A and Ap 4 A as described for human Fhit (18). Initial rates were measured in a Cary 50 spectrophotometer at 25°C.…”
Section: Methodsmentioning
confidence: 99%
“…Like Hint1, Fhit is also a homodimer and tumor suppressor (17). Human Fhit is a Ap 3 A hydrolyase as well as phosphoramidase (18,19). The precise mechanism of action by which it affects tumor development is not well understood, although site-directed mutagenesis studies have indicated that the tumor suppressor function of Fhit is likely not dependent on its Ap 3 A hydrolase activity (20).…”
mentioning
confidence: 99%
“…At the cellular level, FHIT has been shown to induce apoptosis and retard tumor cell proliferation in vitro and in vivo [25,26]. Moreover, it has been established that the FHIT gene encodes a diadenosine polyphosphate (Ap3A) hydrolase [16,19,27]. Therefore, FHIT product is believed to have hydrolytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…The reaction is thought to follow a two-step mechanism, in which a complex of Ap3A and Mg 2+ reacts in the fi rst step with His96 of the enzyme to form a covalent FHIT-AMP intermediate and release MgADP. In the second step, the intermediate FHIT-AMP undergoes hydrolysis to AMP and FHIT [27]. Another suggestion hypothesized by Zhao et al was that the executive mode of the nuclear localization of FHIT protein is due to the binding with other eff ector molecules that have been reported, such as tubulin, Ubc9, Nit, Hint, CDK7, and so on [24].…”
Section: Discussionmentioning
confidence: 99%